Fabrication and characterization of ZnO nanowires by thermal oxidation method - Somvanshi D.; Jit S. (My University, 2025)
Fabrication of ZnO nanowires (NWs) by thermal oxidation method has been studied in this work. The ZnO NWs have been grown by oxidation of Zn metal foil under oxygen environment for two typical oxidation durations. We have investigated the behavior of the as-grown ZnO NWs with the change in oxidation duration at particular temperature. The changes in surface morphology and chemical composition with the variation of oxidation duration have been analyzed by scanning electron microscope (SEM) and energy dispersive spectroscopy (EDS) respectively. From EDS spectra, it is confirmed that Zn metal has completely oxidized into ZnO for higher oxidation duration. In this work, the optimized duration of oxidation for growth of ZnO NWs is found to be ~60 minutes at particular temperature of 600oC. The present method provides a possible mechanism for the growth of ZnO NWs on the p-Si substrates. © (2012) Trans Tech Publications, Switzerland.